Prospective, multicenter, uncontrolled study on the effectiveness and safety of a hyaluronic acid water-based vaginal lubricant in alleviating vaginal dryness and dyspareunia - Manuel Sánchez-Prieto; Carmen Pingarrón; Luciana Bergamaschi; Juan Carlos Bermúdez; José Subiris González; Ruth Sánchez Sánchez; Sílvia Poyo Torcal; Matilde Gómez; María Luisa Ruiz Pérez; Marta Castillo Martínez; M. Eugenia Peña Penedo; Rafael Sánchez-Borrego (Taylor & Francis Group, 2024)
AbstractBackground Vaginal dryness (VD) represents a significant concern affecting women across diverse life stages, encompassing both pre- and postmenopausal women at any age. Dyspareunia, defined by genital pain that can be experienced before, during, or after intercourse, is often associated with vaginal dryness.Aim This study aimed to evaluate the effectiveness and safety of a water-based vaginal lubricant with hyaluronic acid to reduce sexual discomfort associated with vaginal dryness.Methods A prospective, multicenter, uncontrolled clinical investigation was conducted over a three-month period in women aged 18 years or older experiencing pain or difficulty during sexual intercourse for whom the use of a vaginal lubricant was recommended.Results Significant improvements were observed in the FSFI scores, indicating enhanced sexual function (p < .001). Vaginal dryness symptoms, including irritation, dryness, itching, and dyspareunia, significantly decreased after product use (p < .001).Clinical implications This study contributes to the limited scientific knowledge on the application of lubricants in the context of symptoms associated with VD.Strengths & limitations In addition to the short study period, inherent limitations of the study design, and lack of placebo control, it is pertinent to acknowledge that some of the pros used in this study were not based on validated questionnaires. However, as far as we know, this study is the only one that analyzes well-being and sexual pleasure as results using a lubricant formulated with hyaluronic acid.Conclusion This tested vaginal lubricant with hyaluronic acid has demonstrated efficacy in improving vaginal dryness and female sexual function, particularly in reducing pain and improving lubrication during sexual intercourse, and showed a favorable safety profile, with minimal and transient adverse events.